Find the sum of all positive integers a such that for some positive integer b the ratio x a + x 2 − 1 x b + x − 1 is a polynomial in x .
Details and assumptions
If a = 2 , then the denominator is 2 x 2 − 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yes, this was adapted from IMO 2002 Problem 3.
*Note: * This problem has been adapted from IMO 2002 . I took some of the ideas from there to complete my solution.
The case a = 1 will be dealt with separately. For the time being, we let a ≥ 2 .
Let x a + x 2 − 1 x b + x − 1 = P ( x ) . We can rewrite this as x b + x − 1 = P ( x ) ( x a + x 2 − 1 ) It then immediately follows that if C is a root of x a + x 2 − 1 , it must also be a root of x b + x − 1 . Let x a + x 2 − 1 = f a ( x ) . Note that f a ( 0 ) = − 1 < 0 and f a ( 1 ) = 1 > 1 . From IVT, we conclude f a ( x ) must have a root C in the range ( 0 , 1 ) . This must also be a root of x b + x − 1 , so C b + C − 1 = 0 ⟹ C b + C = 1 Again, C is a root of x a + x 2 − 1 , so C a + C 2 − 1 = 0 ⟹ C a + C 2 = 1 Combining them, we find out C a + C 2 = C b + C ⟹ C ( C − 1 ) = C a ( 1 − C b − a ) We know that C a + C 2 − 1 = 0 So C a = 1 − C 2 ⟹ C ( C − 1 ) = ( 1 − C 2 ) ( 1 − C b − a ) Since C = 1 , we can divide both sides by C − 1 to obtain: C = ( C + 1 ) ( 1 − C b − a ) ⟹ C = C − C b − a + 1 + 1 − C b − a ⟹ C b − a + 1 + C b − a = 1 Since 0 < C < 1 , C m > C n for all n > m > 0 . It then follows that if b − a + 1 ≥ a , C b − a + 1 + C b − a < C a + C a − 1 ≤ C a + C = 1 Where in the last step we used the assumption a ≥ 2 ⟹ a − 1 ≥ 1 . This is a contradiction, so a ≤ b − a + 1 .
Now, note that x b + x − 1 = P ( x ) ( x a + x 2 − 1 ) ⟹ x b − a ( x a + x 2 − 1 ) − ( x b + x − 1 ) = ( x b − a − P ( x ) ) ( x a + x 2 − 1 ) ⟹ x b − a + 2 − x b − a − x + 1 = ( x b − a − P ( x ) ) ( x a + x 2 − 1 ) We then conclude x a + x 2 − 1 ∣ x b − a + 2 − x b − a − x + 1
The degree of x b − a + 2 − x b − a − x + 1 is b − a + 2 , which has to be ≥ a . But since b − a + 1 ≤ a , we have two possibilities:
b − a + 2 = b ⟹ a = 2
b − a + 2 = b + 1 ⟹ a = 3
*Case
1
: *
a
=
2
In this case,
f
a
(
x
)
=
2
x
2
−
1
, which has roots
±
2
1
. These must also be the roots of
x
b
+
x
−
1
, so
(
2
1
)
b
=
1
−
2
1
(
−
2
1
)
b
=
1
+
2
1
It can be verified that none of these produce integer solutions for
b
.
*Case
2
: *
a
=
3
We can verify
b
=
5
satisfies the conditions, so
a
=
3
is a solution.
We also have the trivial solution ( a , b ) = ( 1 , 1 ) . The sum of all possible values of a , thus, is 3 + 1 = 4 .
The trivial solution is ( a , b ) = ( 1 , 2 ) , to be exact.
Excellent!A long yet extremely simple-to-understand solution.Just a final question,why is the name of this question Tri-ratio?
Nice Solution, But i wonder how you got from b-a+1>=a to b-a+1<=a in: "The degree of ...... we have two possibilities:" didn't we prove before that b-a+1>= a? and how did you conclude: " b-a+2=b or b-a+2=b+1 "
Log in to reply
Oh, yeah, you're right! This actually gives the bound on b − a ( b − a ≤ 2 ). The last part of my solution is incorrect. However, I believe it is simple comparing coefficients stuff now (I'll edit this comment to include it later). :)
Typo: f a ( 1 ) = 1 > 0
Nice solution.
I simply assumed that for a = 1 there will be at least one polynomial in the form given divisible by that expression. Then, I found b = 5 , a = 3 is another valid solution. Thus, 3 + 1 = 4 . This is NOT a rigorous solution, I was just playing around.
See ISL 2002 N6 . The same problem appeared in a weekly set few months ago. I did solve it, and later I learned from one of my friends that it was an IMO problem 3.
Problem Loading...
Note Loading...
Set Loading...
Let... f ( x ) = x a + x 2 − 1 x b + x − 1
We can rewrite this in the form... x b + x − 1 = ( x a + x 2 − 1 ) ⋅ f ( x )
So we have... f ( x ) = i = 0 ∑ b − a p b − a − i x b − a − i [ p b − a = 1 ]
Now keep noting... :p
( x a + x 2 − 1 ) ∣ ( x b + x − 1 )
∵ x b + x − 1 = x b − a ( x a + x 2 − 1 ) + ( 1 − x ) ( x b − a + 1 + x b − a − 1 )
∴ ( x a + x 2 − 1 ) ∣ ( x b − a + 1 + x b − a − 1 )
∴ de g ( x a + x 2 − 1 ) ≤ de g ( x b − a + 1 + x b − a − 1 ) ⟹ b ≥ 2 a − 1
∵ ( x a + x 2 − 1 ) ∣ ( ( x b − a + 1 + x b − a − 1 ) − x b − 2 a + 1 ( x a + x 2 − 1 ) )
∴ ( x a + x 2 − 1 ) ∣ ( x b − a − x b − 2 a + 3 + x b − 2 a + 1 − 1 ) : = h ( x )
∴ h ( x ) = k ( x a + x 2 − 1 )
Note that, x a + x 2 − 1 is equal to 1 at x = 1 and − 1 at x = 0 ... Hence, it must have a root in the interval ( 0 , 1 ) (if this is the exclusive interval notation, I ain't sure :p)...
Case 2 : b > 2 a − 1 ... But then h ( x ) factorizes as the following, and so it has no roots in the interval ( 0 , 1 ) implying that ( x a + x 2 − 1 ) can't be a factor of h ( x ) ...
h ( x ) = x b − a − x b − 2 a + 3 + x b − 2 a + 1 − 1
= ( x b − a − 1 ) − ( x b − 2 a + 3 − x b − 2 a + 1 )
= ( x − 1 ) ( ( i = 1 ∑ b − a x m − n − i ) − x b − 2 a + 2 − x b − 2 a + 1 )
It's trivial to check that ( a , b ) = ( 1 , 2 ) is another solution, observing the expression...
In total, we have the sum of the values of a : 3 + 1 = 4
Note : This is a very slightly modified version of Problem 3 from IMO 2002 ... I once solved it in this elementary method...